Influence of surfactants in forced dynamic dewetting. Issue 37 (2nd September 2016) - Henrich, Franziska; Fell, Daniela; Truszkowska, Dorota; Weirich, Marcel; Anyfantakis, Manos; Nguyen, Thi-Huong; Wagner, Manfred; Auernhammer, Günter K.; Butt, Hans-Jürgen
Abstract : Surfactants strongly decrease the dynamic receding contact angle even below the critical micelle concentration. The latter is the scaling parameter. Abstract : In this work we show that the forced dynamic dewetting of surfactant solutions depends sensitively on the surfactant concentration. To measure this effect, a hydrophobic rotating cylinder was horizontally half immersed in aqueous surfactant solutions. Dynamic contact angles were measured optically by extrapolating the contour of the meniscus to the contact line. Anionic (sodium 1-decanesulfonate, S-1DeS), cationic (cetyl trimethylammonium bromide, CTAB) and nonionic surfactants (C4 E1, C8 E3 and C12 E5 ) with critical micelle concentrations (CMCs) spanning four orders of magnitude were used. The receding contact angle in water decreased with increasing velocity. This decrease was strongly enhanced when adding surfactant, even at surfactant concentrations of 10% of the critical micelle concentration. Plots of the receding contact angle- versus -velocity almost superimpose when being plotted at the same relative concentration (concentration/CMC). Thus the rescaled concentration is the dominating property for dynamic dewetting. The charge of the surfactants did not play a role, thus excluding electrostatic effects. The change in contact angle can be interpreted by local surface tension gradients, i.e. Marangoni stresses, close to the three-phase contact line. The decrease of dynamic contact angles with velocity follows two regimes. Despite the existence of Marangoni stresses close to the contact line, for a dewetting velocity above 1–10 mm s −1 the hydrodynamic theory is able to describe the experimental results for all surfactant concentrations. At slower velocities an additional steep decrease of the contact angle with velocity was observed. Particle tracking velocimetry showed that the flow profiles do not differ with and without surfactant on a scales >100 μm.